Effectiveness of Sub-Tenon's Bupivacaine Liposome Injectable Suspension for Postoperative Pain Control After Radioactive Plaque Placement for Ciliary Body and Choroidal Melanomas. (July 2017) - Neely, David C.; Mason, Lauren; Crosson, Jason N.; Bray, Kevin J.; McGwin, Gerald G.; Mason, John O.
Purpose: To examine the difference in pain control and systemic pain medication usage with sub-Tenon's bupivacaine versus bupivacaine liposome injectable suspension (BLIS) following radioactive plaque placement for choroidal and ciliary body melanomas. Methods: Retrospective chart review reporting postoperative nurse and physician pain scores, postoperative systemic pain medication usage, and telephone pain survey conducted at a single university institution from January 2016 to October 2016. Results: There were 9 (9 eyes) patients studied who underwent sub-Tenon's bupivacaine injection and 9 (9 eyes) patients who underwent sub-Tenon's BLIS. There were no statistically significant differences on postoperative days 1 to 3 between nurse pain scores, physician pain scores, vision, and average intraocular pressure. The difference in postoperative days 1 and 2 hydrocodone/acetaminophen usage was statistically significant (average pills per day on postoperative day 1 for bupivacaine only 0.22 versus 2.33 for BLIS, P value .0032; and postoperative day 2 for bupivacaine only 0.00 versus 1.00 for BLIS, P value .0289). There were no other statistically significant differences in postoperative systemic pain medication usage. There were no statistically significant differences in telephone pain survey. Conclusion: There was no clinically meaningful difference in postoperative nurse and physician pain scores, postoperative systemic pain medication usage, and telephone pain survey between sub-Tenon's bupivacaine versus BLIS following radioactive plaque placement for choroidal and ciliary body melanomas.